Pengaruh Faktor Audit Tenure, Ukuran Perusahaan Dan Rotasi Audit Terhadap Kualitas Audit - Wandari, Ayu; khairani, Siti (MDP Student Conference, 2024)
This research aims to determine the influence of audit tenure, company size, and audit rotation factors on audit quality, a study of manufacturing companies in the consumer goods industry sector listed on the BEI in 2019- 2022. The theory used in this research is Agency Theory. The approach used in this research is a quantitative approach. The population of this study is the consumer goods industrial sector companies listed on the Indonesia Stock Exchange in 2019 – 2022. The sampling technique uses a purposive sampling technique. The sample used was 20 manufacturing companies listed on the Indonesian stock Exchange. The data analysis technique used is linear regression analysis. Based on the results of partial test research that has been tested, it shows that the variable audit tenure, and company size variables do not have a significant effect on audit quality.